The potential for health - Calman, Kenneth C. (Kenneth Charles) (Oxford : Oxford University Press, 1998)
Can health provision be improved? Can the quality of healthcare be delivered more effectively? Kenneth Calman believes so and shows how, using existing knowledge, the potential for a healthier nation can be achieved.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health -- Great Britain; Health promotion -- Great Britain